Insecticide resistance status of Aedes aegypti in southern and northern Ghana - Anisa Abdulai; Christopher Mfum Owusu-Asenso; Gabriel Akosah-Brempong; Abdul Rahim Mohammed; Isaac Kwame Sraku; Simon Kwaku Attah; Akua Obeng Forson; David Weetman; Yaw Asare Afrane (Parasites & Vectors, 2023)
Abstract Background Outbreaks of Aedes-borne arboviral diseases are becoming rampant in Africa. In Ghana, there is no organized arboviral control programme with interventions restricted to mitigate outbreaks. Insecticide application is a crucial part of outbreak responses and future preventative control measures. Thus, knowledge of the resistance status and underlying mechanisms of Aedes populations is required to ensure optimal insecticide choices. The present study assessed the insecticide resistance status of Aedes aegypti populations from southern Ghana (Accra, Tema and Ada Foah) and northern Ghana (Navrongo) respectively. Methods Phenotypic resistance was determined with WHO susceptibility tests using Ae. aegypti collected as larvae and reared into adults. Knockdown resistance (kdr) mutations were detected using allele-specific PCR. Synergist assays were performed with piperonyl butoxide (PBO) to investigate the possible involvement of metabolic mechanisms in resistance phenotypes. Results Resistance to DDT was moderate to high across sites (11.3 to 75.8%) and, for the pyrethroids deltamethrin and permethrin, moderate resistance was detected (62.5 to 88.8%). The 1534C kdr and 1016I kdr alleles were common in all sites (0.65 to 1) and may be on a trajectory toward fixation. In addition, a third kdr mutant, V410L, was detected at lower frequencies (0.03 to 0.31). Pre-exposure to PBO significantly increased the susceptibility of Ae. aegypti to deltamethrin and permethrin (P < 0.001). This indicates that in addition to kdr mutants, metabolic enzymes (monooxygenases) may be involved in the resistance phenotypes observed in the Ae. aegypti populations in these sites. Conclusion Insecticide resistance underpinned by multiple mechanisms in Ae. aegypti indicates the need for surveillance to assist in developing appropriate vector control strategies for arboviral disease control in Ghana. Graphical Abstract